Development of Student Worksheets (LKPD) Based on the Guided Discovery Learning Model to Improve Students' Reasoning Ability on Class X SPLTV Material - Anisa Dwi Afrianti (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to develop student worksheets based on guided discovery learning models to improve students’ reasoning abilities on the material of a three-variable linear equation system. The quality of this LKPD refers to the valid, practical, and effective aspects. This research uses research and development (R&D) research with ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The subjects in this study were 29 students of class X MIA-1 SMA Imelda Medan.Based on the research that has been done, the results obtained from the validation expert with a percentage of 79% LKPD are in the valid category, while the results from the validation expert with a percentage of 75% RPP are in the valid category. The practicality of the LKPD is seen from the results of the questionnaire responses of mathematics teachers and students with a percentage of 84% and 85% where the percentage is in the very practical category. The effectiveness of LKPD is seen from the results of classical learning completeness with a percentage of 86% where the category is very effective.